(untitled) (Research, Society and Development, 2023)
Objective: To report the experience in the construction of a Libras manual for health professionals - practical guide for professional communication with deaf patients (E-book), product of the Postgraduate program in Health Teaching in the Amazon in the master modality, belonging to the Faculty of state of Pará. Methodology: The construction of the manual took place in the following stages: Literature review and structuring of the manual’s chapters; Textual construction based on the review, study and selection of information to compose the manual; Selection and definition of images; Manual Designer; Final formatting of the manual. Its structuring was done in the Microsoft Power Point program, version 2016, as well as the images registered by the author, and available virtually free of charge.Results: The Libras manual for the health area (E-book) was built, with 34 pages, consisting primarily of images of the basic signs for professional and deaf patient communication in Brazilian Sign Language. Conclusion: We understand that the main challenge in caring for the deaf patient is the communication barrier, due to the lack of preparation and knowledge of professionals. In view of the lack of qualified professionals to meet the demand of deaf patients in our country, it is necessary to build tools that help the process of teaching Libras to health professionals.